Al@C/Expanded Graphite Composite as Anode Material for Lithium Ion Batteries. (1st March 2016) - Huang, Youguo; Lin, Xile; Pan, Qichang; Li, Qingyu; Zhang, Xiaohui; Yan, Zhixiong; Wu, Xianming; He, Zeqiang; Wang, Hongqiang
Abstract: Al@C/expanded graphite was successfully synthesized through a facile method including ultrasonic and heat treatment. In the well-designed three dimensional structure, expanded graphite works as a conductive matrix to support Al particles coated by carbon. The structure integrates the advantages of carbon coating and expanded graphite as conductive support, preserving the electrode activity and integrity and improve the electrochemical performances. Al@C/expanded graphite delivers 657.4 mAh g −1 at 50 mA g −1 and 75.9% capacity retention after 50 cycles. The preliminary results demonstrate that Al@C/expanded graphite is a potential candidate for anode material of lithium ion batteries.